Relationship between impulsivity, aggression and blood ghrelin, vitamin D, lipids levels in borderline personality disorder - Baykara, Sema; Karakas, Sahin; Kaya, Suheda; Akca, Gulay; Telo, Selda (Cukurova Univ, Fac Medicine, 2023)
Purpose: This study aimed to investigate the correlations between impulsivity and aggression, and blood ghrelin, lipids, and vitamin D levels in Borderline Personality Disorder (BPD). Materials and Methods: Thirty female patients with BPD and 30 healthy controls were included to the study. Sociodemographic Data Form, Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Barratt Impulsivity Scale Short Form (BIS-11-SF), Buss-Perry Aggression Questionnaire (BPAQ) were applied.Results: Ghrelin, cholesterol, and triglyceride (TG) levels were higher in BPD patients (p=0.013, p=0.042, p=0.019, respectively); however, there was no significant difference between the groups based on vitamin D, High-density lipoprotein (HDL) and Low-density lipoprotein (LDL) levels. There was no correlation between ghrelin, and lipid and vitamin D levels. The BIS-11 and BPAQ scores were higher in BPD group. A positive correlation was determined between ghrelin and BIS-11 scores. A positive correlation was found between vitamin D and 'anger' subscale score of BPAQ. A negative correlation was identified between triglyceride and the 'verbal aggression' subscale score of BPAQ.Conclusion: BPD is a disorder with several hospital admissions, frequent comorbid conditions, problematic social relationships, and functionality, and the treatment is quite difficult. Regulation of Ghrelin, vitamin D and lipid levels could assist clinicians in the treatment and clinical follow-up of the disease.
Keywords: Borderline personality disorder; impulsive behavior; aggression; ghrelin; vitamin D; lipids